In vitro OECD test methods applied to screen the estrogenic effect of chemicals, used in Korea. (September 2016) - Lee, Hee-Seok; Park, Eun-Jung; Han, Songyi; Oh, Gyeong-Yong; Kim, Min-Hee; Kang, Hui-Seung; Suh, Jin-Hyang; Oh, Jae-Ho; Lee, Kwang-Soo; Hwang, Myung-Sil; Moon, Guiim; Hong, Jin-Hwan; et al.
Abstract: In this study, 27 chemicals found in household products, which became an issue in Korea were screened for the agonistoc and antagonistic effects against human estrogen receptor using official Organization for Economic Cooperation and Development (OECD) in vitro assays, STTA assay using ERα-HeLa-9903 cell line and BG1Luc ER TA assay. In the case of human ER agonist screening by two assays, all tested chemicals did not show agonist effect against ER. In ER antagonist test by BG1Luc ER TA assay, five surfactants α-dodecyl-ω-hydroxypoly(oxyethylene), alcohols C16-18 ethoxylated, nonylphenol, ethoxylated, 3, 6, 9, 12, 15, 18, 21-heptaoxatritriacontan-1-ol, and α-dodecyl-ω-hydroxypoly(oxy-1, 2-ethanediyl)) were found to exhibit weak antagonistic activities. The agonist/antagonist effects against human estrogen receptor of various chemicals, used in Korea by OECD test guideline are reported in this study. These results indicated that two OECD in vitro assays will can be applied in Korea by screening of agonistic/antagonistic effects against human ER of various chemicals. Highlights: OECD in vitro assays applied for screening of the agonistic/antagonistic effect against human ER on 27 chemicals. No chemicals exhibited the agonistic effect against human ER. Five surfactants have been found week antagonistic activities mediated by binding affinity against ER.